The roles of maternal height and body mass index in preterm birth prediction - Fahri Burçin Fıratlıgil; Kazım Emre Karaşahin (Hitit Medical Journal)

(untitled)
Objective: To investigate the role of maternal height and body mass index in the prediction of preterm birthMaterial and Method: Patients who had either cesarean section and/or normal delivery in Department of Obstetrics and Gynecology in the last 5 years were included in the study. Demographic data, weeks of gestation at the time of delivery, maternal height and body mass index of the patients with preterm delivery were recorded retrospectively for the study group. The control group consisted of retrospectively selected patients who had given birth after the expected date of delivery using the Naegele method.Results: In the study, 295 of 541 pregnant women had a preterm birth (study group), while 246 women had given birth after the expected date of delivery (control group). Maternal height and body mass index had an influence on preterm birth. The sensitivity and specificity values for a height of 152.5 cm and a body mass index of 21.3 kg/m2 were (1.0 and 0.13) and (1.0 and 0.06), respectively. In the receiver characteristics analysis of these variables affecting preterm birth, the area under the curve for body mass index and maternal height were 0.763 and 0.708, respectively.Conclusion: We conclude that height and body mass index were found to be good discriminators for the prediction of preterm birth.